Marisela Montenegro, researcher of the Faculty of Psychology at the Autonomous University of Barcelona - Galaz Valderrama, Caterine; Troncoso Pérez, Lelya (Critical Proposals in Social Work, 2021)
Entrevista con Marisela Montenegro, académica de la facultad de Psicología de la Universidad Autónoma de Barcelona